Development of antibacterial cellulosic fabric via clean impregnation of silver nanoparticles. (15th August 2015) - Raza, Zulfiqar Ali; Rehman, Asma; Mohsin, Muhammad; Bajwa, Sadia Zafar; Anwar, Faiza; Naeem, Abdul; Ahmad, Niaz
Abstract: In the present study, we investigate single bath fabrication and impregnation of silver nanoparticles (SNPs) on enzymatic pretreated cotton fabric by using starch both as reducing as well as stabilizing agent under the autoclave conditions of 103.42 kPa, 121 °C for 15 min. The SNPs were characterized using UV–visible (UV–vis) spectroscopy, zetasizer nano and transmission electron microscopy. The UV–vis absorption spectra showed typical absorption peaks at ∼420 nm corresponding to the surface plasmon resonance of SNPs. The hydrodynamic diameter of SNPs was as smaller as 20 nm with their respective zeta potential of −43.20 mV. Both scanning electron and atomic force microscopic analyses revealed that the surface of the treated cotton fabric was rougher than that of untreated fabric, and the SNPs were present on the surface of the treated fabric. Silver mapping and elemental analysis of the treated cotton fabric using energy dispersive X-ray spectroscopy confirmed the presence of SNPs in a homogeneous distribution. The textile properties of the fabric including wettability, whiteness, tensile strength and antibacterial activity were measured by using the standard methods. The SNPs impregnated cotton fabrics showed good durable antibacterial activity against Escherichia coli and Staphylococcus aureus strains. Highlights: We report in situ fabrication/impregnation of silver nanoparticles (SNPs) on cellulose. SNPs were characterized by using spectroscopic and electron microscopic techniques. Porous cellulose matrix of acted as template for SNPs fabrication. Silver mapping of treated fabric confirmed homogeneous distribution of SNPs. The treated fabrics exhibited good antibacterial and other textile properties.